Anti‐OX40L alone or in combination with anti‐CD40L and CTLA4Ig does not inhibit the humoral and cellular response to a major grass pollen allergen. Issue 2 (February 2016) - Gattringer, M.; Baranyi, U.; Pilat, N.; Hock, K.; Klaus, C.; Ramsey, H. E.; Wrba, F.; Valenta, R.; Wekerle, T.
Summary: Background: IgE‐mediated allergy is a common disease characterized by a harmful immune response towards otherwise harmless environmental antigens. Induction of specific immunological non‐responsiveness towards allergens would be a desirable goal. Blockade of costimulatory pathways is a promising strategy to modulate the immune response in an antigen‐specific manner. Recently, OX40 (CD134) was identified as a costimulatory receptor important in Th2‐mediated immune responses. Moreover, synergy between OX40 blockade and 'conventional' costimulation blockade (anti‐CD40L, CTLA4Ig) was observed in models of alloimmunity. Objective: We investigated the potential of interfering with OX40 alone or in combination with CD40/CD28 signals to influence the allergic immune response. Methods: The OX40 pathway was investigated in an established murine model of IgE‐mediated allergy where BALB/c mice are repeatedly immunized with the clinically relevant grass pollen allergen Phl p 5. Groups were treated with combinations of anti‐OX40L, CTLA4Ig and anti‐CD40L. In selected mice, Tregs were depleted with anti‐CD25. Results: Blockade of OX40L alone at the time of first or second immunization did not modulate the allergic response on the humoral or effector cell levels but slightly on T cell responses. Administration of a combination of anti‐CD40L/CTLA4Ig delayed the allergic immune response, but antibody production could not be inhibited after repeated immunization even though the allergen‐specific T cell response was suppressed in the long run. Notably, additional blockade of OX40L had no detectable supplementary effect. Immunomodulation partly involved regulatory T cells as depletion of CD25 + cells led to restored T cell proliferation. Conclusions and Clinical Relevance: Collectively, our data provide evidence that the allergic immune response towards Phl p 5 is independent of OX40L, although reduction on T cell responses and slightly on the asthmatic phenotype was detectable. Besides, no relevant synergistic effect of OX40L blockade in addition to CD40L/CD28 blockade could be detected. Thus, the therapeutic potential of OX40L blockade for IgE‐mediated allergy appears to be ineffective in this setting.